Fractional urinary fluoride excretion in 1.5-3-year-old children - Tatsiana Papruzhenka (Elsevier, 2021)
Aim or Purpose: Currently, due to the lack of data a unified fractional urinary F excretion (FUFE) of 45% is used for all children under 7 yo to assess F intake based on urinary fluoride excretion; the study aimed to investigate FUFE in young children under conditions of varying total daily F intake (TDFI). Materials and Methods: The study recruited 15 children residing in an institution aged 1.5-3.0 years. The material was collected during six two-week periods with different TDFIs: regular and supplemented with table salt with [F] = 150, 200, 250, 300 or 350 mg/kg (in compliance with local regulations). TDFI was assessed through the calculation method of ingested water, food, F-salt and F-toothpaste; the data was obtained through observation. Daily urinary F excretion (DUFE) was assessed through F analysis of 24-hour urine samples using a F-ion-selective electrode. The data were classified into three groups according to children's TDFI level: 1) 0.050-0.149 mgF/kg; 2) 0.150-0.223 mgF/kg; 3) 0.224-0.300 mgF/kg. FUFE was calculated as the ratio between DUFE and TDFI. For statistical analysis, Wilcoxon's t-test was used. Results: In group 1, children had DUFE±SD = 312±187 μgF, in group 2 - 512±162 μgF, in group 3 - 501±185 μgF. FUFE was 0.23±0.03; 0.21±0.07 and 0.16±0.06, respectively (p12<0.01; p13<0.01; p23>0.05). Conclusions: In 1.5-3-year-old children FUFE approaches 23% with a TDFI close to optimal and decreases with a higher TDFI. This is important to consider when calculating TDFI based on FUFE to avoid underestimating the risk of iatrogenic fluorosis.